PD-L1 blockade immunotherapy rewires cancer-induced emergency myelopoiesis - Boumpas, Athina; Papaioannou, Antonis S.; Bousounis, Pavlos; Grigoriou, Maria; Bergo, Veronica; Papafragkos, Iosif; Tasis, Athanasios; Iskas, Michael; Boon, Louis; Makridakis, Manousos; Vlachou, Antonia; Gavriilaki, Eleni; et al. (Frontiers in Immunology, 2024)
Immune checkpoint blockade (ICB) immunotherapy has revolutionized cancer treatment, demonstrating exceptional clinical responses in a wide range of cancers. Despite the success, a significant proportion of patients still fail to respond, highlighting the existence of unappreciated mechanisms of immunotherapy resistance. Delineating such mechanisms is paramount to minimize immunotherapy failures and optimize the clinical benefit. Herein, we reveal that immunotherapy with PD-L1 blockage antibody (αPDL1) in tumour-bearing mice targets the hematopoietic stem and progenitor cells (HSPCs) in the bone marrow (ΒΜ), mediating their exit from quiescence and promoting their proliferation. Notably, disruption of the PDL1/PD1 axis induces transcriptomic reprogramming in HSPCs, from both individuals with Hodgkin lymphoma (HL) and tumour-bearing mice shifting towards an inflammatory state. Functionally, transplantation of HSPCs isolated from αPDL1-treated tumor-bearing mice exhibited resistance to cancer-associated myelopoiesis as evident by the generation of reduced frequencies of myeloidderived suppressor cells (MDSCs) compared to cells from control-treated mice. Our findings shed light on unrecognized mechanisms of action of ICB immunotherapy in cancer, which involves targeting of BM-driven HSPCs and reprogramming of emergency myelopoiesis.